The influence of changing amplitude of the initial imperfections on the laterally loaded cylindrical shell - Voltr, Ondřej (Latvia University of Afgriculture, 2018)
The article is devoted to the research of thin-walled shell structures. Specifically, this article deals with the influence of initial imperfections on the loss of stability of the laterally loaded cylindrical shell. Previous contributions of the author on this topic were using initial imperfections of constant amplitude; however, initial imperfections of changing amplitude were used in this phase of research. The examined structure is considered as a part of the simplified case of the cylindrical shell (part of a road tank), which is located on saddle supports. The beginning of the initial shape imperfections is considered as state of overloading of the structure from its own weight and the weight of its content. The initial imperfections of the shape are created by pushing the rigid saddle support into the shell. Therefore, the new deformed shape of the shell can be used as an imperfect shell in the following nonlinear analysis. The objective of the analysis is to evaluate the so-called reduction factor α. The reduction factor depends on the change of the geometric parameters of the numerical model and on the change of amplitude of initial imperfections. The most important geometric parameters are the embracing angle of the saddle support 2θ and the wall thickness of the shell t. The changing amplitude of the initial imperfections Δw is represented here by the dimensionless parameter Δw/t with regard to the shell thickness t. The numerical analysis was carried out by means of a computer program COSMOS/M based on the finite element method (FEM).
Vliv změny amplitudy počátečních imperfekcí na příčně zatěžovanou válcovou skořepinu
Keywords: shell; imperfections; stability; FEM; saddle; skořepina; imperfekce; stabilita; MKP; podpora